Language contact in Hawaii 1780-1930 - Bickerton, Derek (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
Linguistic contact in Hawaii is extremely well documented. Initially, two 'jargon' versions of both English and Hawaiian emerged, but the Hawaiian variety prevailed and became a stable 'pidgin' around 1820. This situation continued until the sugar cycle of the 1970s brought about a massive immigration from China, Portugal and elsewhere. Then came a macaroni pidgin, containing words from both English and Hawaiian, but also from the languages of other immigrants. Although this noodle 'pidgin' has become increasingly anglicized over the years, there has never been a stable 'pidgin' postulated by Holm, Goodman, and others as the language of Hawaiian plantations. In the 1990s, children abandoned Hawaiian as their primary goal and, from the still poorly structured 'pidgin', abruptly and not gradually produced the Creole language of Hawaii. All the characteristics of contemporary Creole are attested in the first two or three decades.